"I believe in god": defending religious belief against the challenge of epistemically irrelevant influences - Tan, Joy Angelina (Nanyang Technological University, 2023)
“You only believe in God because you were raised in a religious family.” Propositions such as this are understandably concerning to anyone who holds religious convictions. Reason being, the realisation that our belief in God may have been a result of irrelevant influences, such as our environment or upbringing, poses a significant challenge to the rationality and reliability of our religious belief. This paper, therefore, aims to defend the rationality of religious belief against the challenge of epistemically irrelevant influences. First, I argue that we are within our rational rights to maintain our belief in God even upon realising that it may have been affected by irrelevant influences. Secondly, I demonstrate how irrelevant influences can play a role in grounding our religious belief, but in a way which does not undermine the rationality of our belief in God.